Adams–Oliver syndrome review of the literature: Refining the diagnostic phenotype. Issue 3 (4th February 2017) - Hassed, Susan; Li, Shibo; Mulvihill, John; Aston, Christopher; Palmer, Susan
Abstract : The Adams–Oliver syndrome (AOS) is defined as aplasia cutis congenita (ACC) with transverse terminal limb defects (TTLD). Frequencies of associated anomalies are not well characterized. Six causative genes have been identified: ARHGAP31, DOCK6, EOGT, RBPJ, NOTCH1, and DLL4 . We review 385 previously described individuals (139 non‐familial and 246 familial probands and family members) and add clinical data on 13 previously unreported individuals with AOS. In addition to ACC and TTLD, the most commonly associated anomalies included a wide variety of central nervous system (CNS) anomalies and congenital heart defects each seen in 23%. CNS anomalies included structural anomalies, microcephaly, vascular defects, and vascular sequelae. CNS migration defects were common. Cutis marmorata telangiectasia congenita (CMTC) was found in 19% of the study population and other vascular anomalies were seen in 14%. Hemorrhage was listed as the cause of death for five of 25 deaths reported. A relatively large number of non‐familial probands were reported to have hepatoportal sclerosis with portal hypertension and esophageal varices. Non‐familial probands were more likely to have additional anomalies than were familial probands. The data reported herein provide a basis for refining the diagnostic features of AOS and suggest management recommendations for probands newly diagnosed with AOS. © 2017 Wiley Periodicals, Inc.